AB0689 Metabolic syndrome in ankylosing spondylitis and the effect of anti-tnf therapy. (15th June 2017) - Atzeni, F; Gianturco, L; Masala, IF; Bongiovanni, S; Boccassini, L; Sarzi-Puttini, P; Turiel, M
Abstract : Background: Metabolic syndrome (MeS) is a cluster of cardiovascular (CV) risk factors (obesity, dyslipidemia, hypertension, alterations in glucose metabolism, and insulin resistance) whose prevalence is increasing particularly in devoloped countries. In comparison with the general population, patients with ankylosing spondylitis (AS) are at increased risk of cardiovascular (CV) disease, which is one of the main causes of mortality among them. Objectives: The aim of this study was to identify the relationship between MeS and disease activity in AS patients, and evaluate the the effect of anti-tumour necrosis factor (TNF) therapy. Methods: The study involved 30 outpatients who met the New York diagnostic criteria for AS: 14 males and 16 females; mean age 53.07±10.73 years; mean disease duration 5.03±4.06 years. All of the patients were being treated with DMARDs and anti-inflammatory drugs, but none had received any biological agents or steroids at baseline. The patients underwent laboratory tests (lipid profile and glucose levels), a clinical and standard echocardiographic examination, carotid ultrasonography (including the assessment of intima-media thickness and pulse wave velocity), and speckle tracking echocardiography (STE) of the left ventricle (LV) using Philips QLAB software to evaluate their CV risk profiles. Functional impairment and disease activity were assessed using the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and the Bath Ankylosing Spondylitis Functional Index (BASFI). All of the patients were evaluated at baseline and after 12 months of anti-TNF treatment. The data were statistically analysis using non-parametric chi-squared and Mc-Nemar tests, and the Wilcoxon-Mann-Whitney test. Results: Before starting anti-TNF therapy, the cohort was divided into two groups: those with MeS (25%) and those without. The patients with MeS higher BASDAI scores (chi-squared test: 4.85; p=0.03). After 12 months of follow-up, there was a statistically significant improvement in global longitudinal strain (GLS) in both groups: from a baseline median of 19.94 (IQR 18.66–20.78) to a median of 21.46 (IQR 20.37–22.69) (p=0.02) in the non-MeS group, and from a baseline median of 18.88 (IQR 16.00–19.35) to 19.54 (IQR 18.21–19.98) (p=0.04) in the MeS group. No other changes in CV parameters were observed. The improvement in BASDAI scores was greater in the MeS group, but the difference was not statistically significant. The prevalence of MeS decreased after 12 months of anti-TNF therapy, although the McNemar test showed that the decrease was of borderline significance (p=0.048). Conclusions: AS patients are affected by MeS. The effects of anti-TNF drugs on MeS are still controversial, but our findings suggest that they improve CV markers such as GLS as well as disease activity. The main limitation of this study is its small sample size and short follow-up; further studies are required in order to clarify the influence of MeS on clinical therapeutic outcomes. Disclosure of Interest: None declared